Fucus vesiculosus extracts as natural antioxidants for improvement of physicochemical properties and shelf life of pork patties formulated with oleogels. (17th April 2019) - Agregán, Rubén; Barba, Francisco J; Gavahian, Mohsen; Franco, Daniel; Khaneghah, Amin Mousavi; Carballo, Javier; Ferreira, Isabel CFR; da Silva Barretto, Andrea Carla; Lorenzo, José M
Abstract: BACKGROUND: There is limited information in the literature concerning the feasibility of using algal extracts as natural additives for improvement of the quality and shelf‐life of meat products. Hence, a Fucus vesiculosus extract (FVE) at the concentrations of 250 mg kg ‐1 (FVE‐250), 500 mg kg ‐1 (FVE‐500) and 1000 mg kg ‐1 (FVE‐1000) were added to pork patties with linseed oil oleogel as a fat replacer. RESULTS: Total polyphenol content of FVE was determined to be 20 g phloroglucinol equivalents 100 g ‐1 extract. Antioxidant values ranged from 37.5 μmol of Trolox equivalents (TE) g ‐1 (FRAP assay) to 2111 μmol TE g ‐1 extract (ABTS assay). Regarding oxidation stability, FVE‐1000 showed the lowest values of thiobarbituric acid‐reactive substance and carbonyl content. On the other hand, FVE did not improve color, surface discoloration or odor attributes of patties during storage. Sensory evaluation revealed that there was no significant difference among all studied samples. CONCLUSION: Although FVEs have a high polyphenol content and antioxidant activities, they are not effective oxidation inhibitors for long‐term storage of meat products. Therefore, additional measures or compounds should be considered when FVE is the only antioxidant in meat products. © 2019 Society of Chemical Industry